Raising the flag of vigilance on Mpox outbreak in Indonesia: are we prepared? - Adnyana, I Made Dwi Mertha; Maulana, Sidik; Lutfian, Lutfian; Adiwinoto, Ronald Pratama (PT. Mega Science Indonesia, 2024)
In the wake of the COVID-19 pandemic, the world has become acutely aware of the devastating impact of infectious diseases on public health, economies, and societies. As we gradually recover from the aftermath of COVID-19, another potential threat looms on the horizon, mpox, formerly known as monkeypox. The recent surge in mpox cases worldwide has prompted health authorities to sound an alarm, and Indonesia, as a populous nation with a complex healthcare system, must ask itself: Are we prepared for this emerging challenge?. The question